The changing role of surgery in metastatic non-seminomatous germ cell tumour. - Cassidy, J. (Nature Publishing Group, 1992)
In the last 2 years (1989-1990) we have treated a total of 53 patients with metastatic nonseminomatous germ cell tumours (teratoma). In ten cases surgery to remove residual abdominal masses was required on completion of chemotherapy and normalisation of tumour markers (HCG and AFP). In a further three patients with large intra-abdominal masses and little or no other sites of disease surgery was performed as a therapeutic intervention, in the context of plateauing or rising tumour markers despite intensive chemotherapy. In all three, this approach resulted in a rapid fall in tumour markers, and following further chemotherapy all three remain disease free at 7, 12 and 25 months. For this small sub-group of patient failing to respond to chemotherapy who have resectable lesions, interventional surgery should be considered as part of a combined approach to treatment.